Mexico : Public Expenditure Review, Volume 1. Core Report - World Bank (Washington, DC, 2013)
This Public Expenditure Review (PER) concentrates on four main issues: the overall fiscal sustainability and rigidities in expenditure, the distribution of benefits of public spending across households with different income levels, the geographic distribution of the spending, and the institutions for budgeting and expenditure management. Thus, it is not a traditional public expenditure review (PER), with extensive analysis of spending efficiency and institutions in individual sectors. Such analysis is anticipated as a follow-up to this report, such as with PERs on Infrastructure, Health and Education. A central part of this report concerns the analysis of benefit incidence to evaluate the impact of public expenditures as well understanding the incidence of taxes, existing and proposed. Understanding the expenditure programs' differing distributions of benefit across income groups can help to evaluate their priority. This, in turn, can help bring agreement about fiscal reform on the tax side. People will agree to pay more if there is consensus that expenditures are effective and help the poor. These are the concerns of Chapter 2. Another concern is the geographic distribution of public spending. Almost all the resources available to states and municipalities (except for the Federal District, DF) come from the federal government. Compared with 1992, sub-national governments now get transfers for about twice as much per capita in real terms. Chapter 3 deals with the geographic-distribution issues. Finally, the fourth chapter concerns the institutions for budgeting and expenditure management.